Answer:
0.0837 kJ/K
Step-by-step explanation:
Given:
Temperature of the cold reservoir T,cold = 600 K
Temperature of the hot reservoir T,hot= 1200 K
Heat transferred , Q=100 kJ
Now the entropy change for the cold reservoir
![\bigtriangleup S,cold=-(Q)/(T,cold)](https://img.qammunity.org/2020/formulas/engineering/college/55ra3cm9t3dld5gj3gtjvtmz828wi79w38.png)
![\bigtriangleup S,cold=-(-100)/(600)](https://img.qammunity.org/2020/formulas/engineering/college/rlc6rmlhjtpqyi45cz3we2ft1xzi2zua1x.png)
![\bigtriangleup S,cold=0.1667 kJ/K](https://img.qammunity.org/2020/formulas/engineering/college/k97iv0a63oylt5lotjo45vv7kq1jl6515n.png)
Now the entropy change for the cold reservoir
![\bigtriangleup S,hot=-0.0833 kJ/K](https://img.qammunity.org/2020/formulas/engineering/college/acjyirh0nuvfmzhpzedknitn3zjo268z2l.png)
Therefore, the total entropy change for the two reservoir is
![\bigtriangleup S=\bigtriangleup S,hot +\bigtriangleup S,cold](https://img.qammunity.org/2020/formulas/engineering/college/xicatcmgiaruiwokky467gwrmfxwkd4m5u.png)
thus,
ΔS=0.1667-0.0833
ΔS=0.0833 kJ/K
Since, the change of entropy is positive thus we can say it is possible and
increase of entropy principle is satisfied